EXOCRINE PANCREATIC INSUFFICIENCY IN CHILDREN WITH TYPE 1 DIABETES MELLITUS: A NEW PROBLEM OF PEDIATRIC GASTROENTEROLOGY - A. A. Nizhevich; G. M. Yakupova; O. A. Malievskii; E. N. Akhmadeeva; A. M. Farkhutdinova (Вопросы современной педиатрии)
One of the complications of diabetes mellitus is the development of pancreatic exocrine insufficiency. Fecal elastase 1 is a good marker of pancreatic exocrine secretion. The aim of the study was to evaluate the pancreatic exocrine secretion in children with type 1 diabetes mellitus with fecal elastase 1 test to estimate the possible need for exogenous pancreatic enzyme replacement therapy. The exocrine pancreatic function was evaluated in 54 diabetic children on the basis of steatocrite test and a determination of fecal elastase 1 concentrations. Compared to the controls, the diabetic children had significantly lower levels of fecal elastase 1 concentration (p<0,001). Steatorrhoea was registered in all patients with fecal elastase 1 level < 200 µg/g stool. All those patients were treated with pancreatin (creon) for 1 month. A reduction of fat excretion was observed in the pancreatin treated group at the end of the study. Pancreatin replacement therapy can be used safely in children with type 1 diabetes mellitus associated with exocrine pancreatic insufficiency.